The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1590/1678-775720130472
|View full text |Cite
|
Sign up to set email alerts
|

Postretention stability after orthodontic closure of maxillary interincisor diastemas

Abstract: Anterior spaces may interfere with smile attractiveness and compromise dentofacial harmony. They are among the most frequent reasons why patients seek orthodontic treatment. However, midline diastema is commonly cited as a malocclusion with high relapse incidence by orthodontists.ObjectivesThis study aimed to evaluate the stability of maxillary interincisor diastemas closure and the association of their relapse and interincisor width, overjet, overbite and root parallelism.Material and MethodsSample comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 16 publications
(28 reference statements)
2
30
3
Order By: Relevance
“… 4 15 However, some mesial inclination of central incisors is preferred. 14 One follow-up study reported relapse of median diastema in 49% patients and found wider initial width of diastema and fremitus of maxillary incisors strongly associated with space opening. 16 Though the prevalence of mesiodens is reported to be only 0.15 to 2.2% of the population with a preference to males, 17 their presence in the maxillary arch could be deleterious from the esthetic and functional points of view.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 4 15 However, some mesial inclination of central incisors is preferred. 14 One follow-up study reported relapse of median diastema in 49% patients and found wider initial width of diastema and fremitus of maxillary incisors strongly associated with space opening. 16 Though the prevalence of mesiodens is reported to be only 0.15 to 2.2% of the population with a preference to males, 17 their presence in the maxillary arch could be deleterious from the esthetic and functional points of view.…”
Section: Discussionmentioning
confidence: 98%
“…Another study found midline diastema recurrence in 60% of the sample with stronger correlation of relapse with larger initial diastema width, relapse of overjet, and intermaxillary osseous cleft and concluded that midline diastema closure is highly unstable, hence, needs lifetime wear of maxillary fixed retainer. 14 Inadequate root parallelism at the end of treatment has been also cited as a reason for median diastema relapse. 4 15 However, some mesial inclination of central incisors is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…While midline diastema relapse occurred in 60% of the sample, lateral diastemas closure remained stable after treatment. Only initial diastema width and overjet relapse showed association with relapse of midline diastema [46].…”
Section: Morais Et Al Reported No Association Between Relapse Of Intmentioning
confidence: 91%
“…Depending on the aetiology, the treatment may also take place in a different way, i.e. orthodontic treatment [13,17,24] or surgical treatment [32,34] of diastema.…”
Section: Introductionmentioning
confidence: 99%